BAHASA DAN GENDER DALAM MASYARAKAT MELAYU DI PEDALAMAN KALBAR - Yusriadi Yusriadi (PSGA LP2M IAIN Pontianak, 2018)
Observers often consider that the Malay society lack of attention to aspects of gender. They use German, English, Francis, or Arabic, as comparisons. This article is presented to illustrate how gender aspects are considered in Malay language and society. The data are collected from Malay speakers in the rural area of Kapuas Hulu, West Kalimantan, shows that gender aspects are actually present in the language and culture of society. The community knows the concept or words of the pemali to maintain deviant behavior among women and men. Language-speaking communities also have vocabulary to show the division of tasks between women and men, and are reinforced by distinctive narratives found in folklore. These data show that gender aspects are actually felt and important in Malay language and society, especially Malay communities. [Para pemerhati sering menganggap masyarakat Melayu kurang memberikan perhatian pada aspek gender. Mereka menggunakan bahasa Jerman, Inggris, Francis, atau Arab, sebagai pembandingnya. Artikel ini disajikan untuk menggambarkan bagaimana aspek gender diperhatikan dalam bahasa dan masyarakat Melayu. Data yang dikumpulkan dari penutur bahasa Melayu di pedalaman Kapuas Hulu, Kalbar, menunjukkan bahwa aspek gender sebenarnya hadir dalam bahasa dan budaya masyarakat. Masyarakat mengenal konsep atau kata-kata pemali untuk menjaga prilaku menyimpang dari kalangan perempuan dan lelaki. Masyarakat penutur bahasa juga memiliki kosa kata untuk menunjukkan adanya pembagian tugas perempuan dan lelaki, serta diperkuat dengan narasi yang distingtif terdapat dalam cerita rakyat. Data ini menunjukkan bahwa aspek gender sebenarnya dirasakan dan penting dalam bahasa dan masyarakat Melayu, terutama masyarakat Melayu di pedalaman Kapuas Hulu, di Kalimantan Barat].